"Teaching" the therapeutic alliance: on peeling a banana with a knife and fork. (December 2014) - Chazan, Lynette
Objective: This paper discusses the implications for training of the centrality of the therapeutic alliance to the practice of psychiatry. Conclusion: Recent research highlights the centrality of the therapeutic alliance, not only to positive outcomes across the psychotherapies but in all psychiatric practice. This understanding, along with a cultural shift toward psychological-mindedness, suggests that we teach relational as well as intellectual skills and implement a broader role for psychotherapy training. A subsequent article will address the question of whether and how such skills can be developed.